The Effectiveness of Using Application as An Online Basic Computer Learning Medium in Higher Education Institution - Mu’azah Md. Aziz; Yusuff Adeola Moshood; Ainul Maulid Ahmad, (International Journal of Interactive Mobile Technologies (iJIM), 2022)
The use of Google Meet (GM) application for teaching and learning implementation online is one of the methods in the teaching manual that has been introduced by the Ministry of Higher Education (MOHE). This study aimed to identify the level of readiness of students and self-motivation by students when using the GM application as a medium for online learning Basic Computer subject in Higher Education Institution during pandemic Covid-19. A quantitative study was conducted with the participation of 43 students from Diploma level in Universiti Islam Antarabangsa Sultan Abdul Halim Mu’adzam Shah (UniSHAMS). A set of questionnaires had been provided with three main categories consists of Online Learning Medium, Online Learning Method Using Application, and Relationship Between Online Learning Application’s Features with Self-Motivation. The findings of this study show that Online Learning Medium improves self-motivation and directly encourages students to adopt technology into their learning. Furthermore, learning application directly affects their self-motivation. Online learning medium, as mediated by online learning application, can affect self-motivation. The results suggested that MOHE must encourage the use of online learning application for teaching and learning in their schools to align with the technology growth rapidly.